A study on customer satisfaction towards services provided by Kota Belud hotel / Justin Dongeh - Dongeh, Justin (2011)
This study attempts to identify the customer satisfaction towards all services provided by Kota Belud Hotel at this point in time . Researcher wants to determine the demographic characteristics of KBH customers as well as its major profiles. Apart from that this study also tries to investigate customer preferences of services from the hotel and whether the customers are impressed with the services rendered. Survey method is deployed by the research to solicit information form respondents who are mostly KBH customers. There are some positive finding as to the services provided by the hotel, especially the rooms, environment, ambience and staff performance. Nonetheless, there are some problems encountered by customers and a few recommendations have also been suggested to resolve the problems.